Daytime Sleep and Parenting Interactions in Infants Born Preterm - Schwichtenberg, A. J. (2011)
OBJECTIVE: Following a transactional perspective, this longitudinal study assessed concurrent and time-lagged associations between infant daytime sleep behaviors and maternal play interactions within a sample of infants born preterm. METHOD: Data were collected from 134 families recruited from 3 Wisconsin NICUs. Multiple methods were used to collect data at infant NICU discharge and when infants were 4, 9, and 24 months postterm, including parent-report infant sleep logs, family sociodemographic assets and a 15 minute video-taped play session. RESULTS: Within time points, infants who napped more had mothers who were rated as more positive and communicative or less negative during play interactions at 4, 9 and 24 months compared to infants who napped less. Time-lagged findings indicated that infants who took more naps experienced more optimal maternal interactive behaviors later in development than infants who took fewer naps. Additionally, mothers who expressed more negative affect at 4 months or 9 months predicted more infant daytime sleep later in development. CONCLUSION: Previous studies document that nighttime parent-child interactions influence nighttime sleep. This study presents the natural extension that daytime sleep influences daytime interactions. The present study draws attention to the understudied area of daytime naps in young children and provides support for the longitudinal bi-directional processes between sleep and parenting interactions.